Karyological Studies in Some Species of the Genus Silene (Caryophyllaceae) - (:unkn) unknown (UNIV TOKYO CYTOLOGIA, 2009)
Karyology of the 6 Silene species from Turkey was investigated. Diploid chromosome numbers and the basic chromosome number of the studied taxa were obtained as 2n=24 and x=12 respectively. The karyotype analysis of S. viscosa, S. eremitica, S. skorpilii and S. confertiftora were carried out for the first time. Also the chromosome numbers of S. eremitica and S. confertiflora were determined for the first time. The largest chromosomes were observed in S. otites and the smallest ones were observed in S. viscosa. S. otites shows the highest A(1) index. S. skorpilii represents the highest interchromosomal asymmetry coefficient (A(2)). The karyologic results oh the study and the analysis of chromosomal morphology of each taxon were shown as tables.
Keywords: Caryophyllaceae; Chromosome; Karyology; Silene; SOUTH ANATOLIA; EAST ANATOLIA; L. CARYOPHYLLACEAE; TAXA